RATIONAL EMOTIVE BEHAVIOR THERAPY SEBAGAI ALTERNATIF PEMULIHAN TRAUMA BAGI KORBAN KEKERASAN DALAM PACARAN - Sari, Fitri Kurnia; Wijono, Sutarto; Hunga, Arianti Ina Restiani (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2020)
One of the effects of violence in courtship is that the victim experiences trauma. The purpose of this literature review is to explain how the REBT psychotherapy approach can be used to recover trauma from victims of dating violence. Through the literature review method, discussions about REBT therapy in the recovery of trauma victims are carried out. Trauma has a negative impact on victims, in this case adolescents because it will affect the decline in thinking, emotional, and behavioral. To overcome trauma, recovery is needed to cure victims of violence in courtship, so that they can live their lives normally again. Factors of thoughts, feelings, and behavior are fundamental to the approach with REBT. These three factors are related to disorders caused by trauma. The conclusion from the discussion shows that Rational Emotive Behavior Therapy can be used to recover trauma from survivors of violence in dating relationships.